Safety and feasibility assessment of implantable chest wall venous access port for patients with acute leukemia - Ke, Peng; Liao, Min; He, Fan; Xu, Ying; Li, Guoqiang; Hu, Lina; Feng, Chun; Zhang, Ruiting; Ding, Yanhong; Zhou, Jihao; Lu, Jialing; Cao, Yixuan (Frontiers in Oncology, 2026)
BackgroundTotally implantable venous access ports (TIVAPs) are widely used in chemotherapy for solid malignant tumors. However, there are currently few data on the application of TIVAPs in patients with acute leukemia. The purpose of this study was to evaluate the safety and feasibility of TIVAPs in patients with acute leukemia.MethodsA single-institute retrospective review was performed on 94 adult patients with acute leukemia who underwent TIVAPs at Shenzhen People’s Hospital between January 2020 and April 2025. Baseline characteristics and TIVAP-related complications were evaluated.ResultsAmong of 94 patients, all TIVAPs were successfully implanted. No intraoperative complications occurred. Early postoperative complications (less than 30 days postoperatively) occurred in five (5.3%) patients, including local subcutaneous hematoma (n=3, 3.2%) and infection (n=2, 2.1%). Only two patients (n=2, 2.1%) developed late postoperative complications (more than 30 days postoperatively), including one catheter-related deep vein thrombosis and one catheter dysfunction. Three of 94 patients (3.2%) required premature TIVAPs removal due to localized bleeding complications or catheter-related bloodstream infection. As of June 1, 2025, the median dwelling time of TIVAPs was 26.6 months (range: 0.1-76.4 months). The 2-year of cumulative hematoma-free catheter survival rates was 96.8% ± 1.81%. The 2-year of cumulative adverse event-free catheter survival rates was 93.5% ± 2.55%.ConclusionsOur study shows that TIVAP can provide a safe and effective system for long-term intravenous treatment of patients with acute leukemia. Therefore, TIVAP is another potentially effective and safe option for patients with acute leukemia.